Diseño de un programa de orientación académica y profesional para las mujeres en riesgo de exclusión social - Rufino Cano González (Universidad de La Rioja, 2013)
Despide being an old matter, once begun the XXI century, not only has not the problem despaired, but also it has increased due to a lack of alternatives. Governments and Administrations do not dare or they do not want to talk about the matter and prefer to maintain a ambiguous attitude when offering different type of solutions. We believe thatch it is absolutely necessary to go deeper into theoretical debate, listen to the main characters and go forward in public policies which promote alternatives, for their poverty, labor, economic, social and change of life for these women. Subsequently, it is necessary to develop social welfare programmers, which can remedy poverty and unemployment, essential in order to satisfy the demand of these work ring women. Our offer, enriched by other type of actions towards economic and social foundations, basing these structures, supports a development of vocational and educational guidance in order to make easier for these women to go out and integrate themselves in a social and labor community of citizens.